The Impact of Lack of Resources on Declining Students’ Enrolments in Design and Technology in Botswana Junior Secondary Schools - Gaotlhobogwe, Michael (Design and Technology Education: An International Journal, 2012)
Lack of resources has resulted in declining students’ enrolment in design and technology in Botswana junior secondary schools by up to 6% per year over 10 years, despite positive encouragement by the government. Based on the PATT (pupils’ attitude towards technology) theoretical framework this study indicated how a lack of resources in Botswana junior secondary schools impacted upon students’ attitudes towards design and technology. Research from most parts of the world indicates that attitudes toward technology is increasingly becoming an important area of research as the impact of technology on society increases. Technological impact on society has resulted in a shift of perceptions about the role of technology education the world over. Views of students expressed during focus group interviews and analysed through a hybrid of a data driven inductive approach and deductive a priori template of codes approach indicated that lack of resources impacted upon students’ enjoyment and performance of Design and Technology.